Pengaruh Employee Engagement, Inklusivitas Organisasi, Dan Kolaborasi Terhadap Loyalitas Pegawai Pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kota Medan - Barus, Yossi Br; Normi, Siti; Panjaitan, Maludin (JOURNAL ECONOMICS AND STRATEGY, 2025)
This study aims to test and analyse the effect of employee engagement, organisational inclusiveness, and collaboration on employee loyalty at the Medan City Human Resources Staffing and Development Agency. The research method used in this research is quantitative descriptive research method. The sample in this study were all employees of the Civil Service Agency and Human Resources Development of Medan City, totalling 67 employees because of the small sample size, the authors used the saturated sampling technique. Based on the results of the t hypothesis test, it can be concluded that employee engagement has a positive and significant effect on employee loyalty, organisational inclusiveness has a positive and significant effect on employee loyalty, collaboration has a positive and significant effect on employee loyalty. Based on the results of the F hypothesis test, it can be concluded that employee engagement, organisational inclusiveness, and collaboration simultaneously have a positive and significant effect on employee loyalty. Based on the results of the coefficient of determination analysis, the Adjusted R Square is 0.685, which means that the employee loyalty variable can be explained by the employee engagement, organisational inclusiveness, and collaboration variables in this study by 68.5%, while the remaining 31.5% is other variables or factors.